Occasional actualization of idioms as the way of creation of the comic effect (on the basis of the French language) - D A Yanenko (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
In the given article the author analyses the comic potential of idioms and their occasional actualizations, investigates the abilities of idioms to create an ironical tonality of the text and to have the similar influence on the addressee, studies the pragmatical mechanism of achievement of the comic effect on the basis of various types of actualization of idioms on a material of modern play J.M. Florensa «Les joyeuses et horrifiques farces du Père Lalande».